Tolerability and Efficacy of Post-Transplant Cyclophosphamide in Older Adults Undergoing Matched Sibling Donor Allogeneic Transplantation: A Retrospective Analysis - Desai, Nihar; Alfaro Moya, Tommy; Novitzky-Basso, Igor; Pasic, Ivan; Lam, Wilson; Michelis, Fotios; Gerbitz, Armin; Viswabandya, Auro; Kim, Dennis Dong Hwan; Kumar, Rajat; Mattsson, Jonas; Law, Arjun (Blood, 2024)
Introduction: Post-transplant cyclophosphamide (PTCy) is a safe and effective graft versus host disease (GVHD) prophylaxis strategy. While initially established as the standard of care for haploidentical allogeneic hematopoietic cell transplantation (alloHCT), its use is now expanding to HLA-matched unrelated donors (MUD), and HLA-matched sibling donors (MSD) alloHCT. However, there is limited evidence of its safety in older adults (>60 years). We evaluated the tolerability of PTCy in older adults undergoing alloHCT from a MSD and compared the outcomes with an older cohort using a conventional regimen of calcineurin inhibitor (CnI) and methotrexate (MTX). Methods: We retrospectively analyzed patients receiving MSD alloHCT between August 2010 and March 2023. Overall survival (OS) and GVHD-free/relapse-free survival (GRFS) were estimated using the Kaplan-Meier method and the difference between groups was assessed using the log-rank test. Cumulative incidences (CI) of relapse (CIR), Non-relapse Mortality (NRM), acute and chronic GVHD, and bloodstream infections (BSI) were analyzed using competing risk models. A p-value of <0.05 was considered statistically significant and analyses were performed using EZR (version 1.62). Results: One-hundred and two patients underwent MSD alloHCT. The standard GVHD prophylaxis regimen for MSD alloHCT was a combination of CnI and MTX (n=69) between August 2010 and June 2019. Starting in June 2019, the GVHD prophylaxis protocol was revised to PTCy, CnI, and mycophenolate mofetil (MMF) (n=33). The baseline characteristics were similar between the groups except for a higher use of cryopreserved grafts in the CnI+MTX group (65.2 % vs 3%; p<0.001). The median follow-up after alloHCT was 16.4 months (11 - 22) for the PTCy group and 41 months (34 - 48) for the Cni-MTX group (p=0.001) The median age of the cohort was 65 years (62 - 68), and 58 (56.8%) were male. Acute myeloid leukemia was the most common indication for alloHCT (n=57, 55.9%). The majority (n=99, 97%) received reduced-intensity conditioning. Peripheral blood was the graft source for all patients, with a median CD34+ cell dose of 6.5 x 106/kg (5.6 - 7.9). The median time to neutrophil engraftment was 19 days (17-21) in the PTCy group versus 17 days (16-19) in the Cni+MTX group (p=0.22). The median time to platelet engraftment was 20 days (18-27) for PTCy and 16 days (14-18) for the Cni+MTX group (p=0.09). Graft failure occurred in 2 patients (1.9%), both in the CNI+MTX group. The median time to discontinuation of immunosuppression was 82 days (69-107) in the PTCy group and 139 days (100-282) in the CnI+MTX group (p=0.008). At D+100, the CI of aGVHD grade II-IV was significantly lower in the PTCy group [25.3% (11.7 - 41.5) vs 29.3% (19 - 40); p=0.04]. There was no significant difference in grade III-IV acute GVHD between the groups [8% (range: 1.3-23) vs. 8.3% (range: 3-17); p=0.15]. Moderate to severe cGVHD occurred in 35.8% (12.5-60.3) of the PTCy group versus 51.5% (38.6-62.9) in the CnI-MTX group (p=0.14). The CI of clinically significant CMV viremia (>500 IU/mL) at D+100 was 36.4% (20 -52) in the PTCy group and 36.2% (25 - 47) in the CnI+MTX group; p=0.67. No patient developed CMV end organ damage. There were 2 episodes of EBV reactivation, both in the PTCy group. The D+100 incidence of BSI was 60.6 % (42 - 75) and 17.4% (10 -27) in the PTCy and CnI+MTX groups, respectively (p<0.001). The NRM at 1 year was 9.7% (2 - 23) and 31.9% (21 - 43) in the PTCy and CnI+MTX groups, respectively (p=0.04). The CI of relapse at 2 years was 28.2% (12-47) for the PTCy group and 17.4% (9 -27) in the CnI+MTX group (p=0.4). The GRFS at 1 year was 40% (22 - 57) in the PTCy group versus 5.4% (2 - 13) in the Cni+MTX group (p=0.003). The OS at 2 years was 54.8% (31-73) in the PTCy group and 46.4% (34-58) in the CnI+MTX group (p=0.28). Conclusion: PTCy significantly reduces the incidence of acute GVHD and NRM, while improving GRFS in older adults undergoing MSD alloHCT. However, patients receiving PTCy have higher rates of bloodstream infections. PTCy shows comparable rates of viral reactivation, relapse, and OS to conventional regimens. The delayed engraftment for platelets and neutrophils does not correlate with a higher incidence of graft failure. Further studies are warranted to validate these findings. Kim:Pfizer: Honoraria, Research Funding; Ascentage: Consultancy; Paladin: Honoraria, Research Funding; Novartis: Honoraria, Other: Advisory board, Research Funding.